Reading processes of public and private middle school and high school students - de Oliveira, Adriana Marques [UNESP]; Santos, Jair Lício Ferreira; Capellini, Simone Aparecida [UNESP] (Springer Nature, 2024)
Introduction: Reading has been widely discussed, mainly due to the published results of international performance tests of schoolchildren. The gaps generated in literacy hinder the development of basic skills necessary for reading, which will have a negative impact on the teaching-learning process from elementary school to high school. This study aimed to compare the reading performance of the students in public and private schools through tests of the Brazilian reading processes-PROLEC-SE-R. Methods: Cross-sectional study. The Brazilian adaptation of the PROLEC-SE-R was administered to 436 students: 221 from the state school (G1 6th year, n = 30; G2 7th year, n = 33; G3 8th year, n = 35; G4 9th year, n = 31; G5 1st year, n = 32; G6 2nd year, n = 30; G7 3rd year, n = 30) e 215 private schools (G8 6th year, n = 31; G9 7th year, n = 31; G10 8th year, n = 30; G11 9th year, n = 31; G12 1st year, n = 30; G13 2nd year, n = 31; G14 3rd year, n = 31). Tools of descriptive and bivariate analysis were used. Results: Superior performance of the private school students on spelling tests helps their reading as evidenced by their scores for syntactic and semantic processes. When the knowledge of the use of the word in text, extraction of meaning and its understanding was needed, the difficulty of access to the mental lexicon of the studied population became evident. Conclusion: The PROLEC-SE-R, in addition to establishing the reading profile of elementary and high school students, shows that the gaps in teaching and learning, which exist between public and private education in the literacy period, accompany students throughout the basic education cycle. Knowing the reading profile and in which process there is a disruption is important so that the teaching of specific strategies can be promoted throughout the entire schooling process, especially in primary and secondary education.
Keywords: Adolescence; Elementary school; Evaluation; High school; Reading process